1999
DOI: 10.1104/pp.121.4.1081
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Expression of Four Proline-Rich Cell Wall Protein Genes in Arabidopsis Encoding Two Distinct Subsets of Multiple Domain Proteins

Abstract: We have characterized the molecular organization and expression of four proline-rich protein genes from Arabidopsis (AtPRPs). These genes predict two classes of cell wall proteins based on DNA sequence identity, repetitive motifs, and domain organization. AtPRP1 and AtPRP3 encode proteins containing an N-terminal PRPlike domain followed by a C-terminal domain that is biased toward P, T, Y, and K. AtPRP2 and AtPRP4 represent a second, novel group of PRP genes that encode two-domain proteins containing a nonrepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 54 publications
2
68
0
Order By: Relevance
“…The majority of CL-EXTs identified in Arabidopsis are not predicted to be GPI-anchored (see Table I and Supplemental Table S2 in Johnson et al, 2017), and consistent with this, only a few GPI-anchored EXTs (class 9) were observed in Phytozome and 1KP data. Only one class, GPI-anchored PRPs (class 14), had no representatives from any 1KP group, which is consistent with our current, albeit limited, knowledge of PRPs (Averyhart-Fullard et al, 1988;Datta et al, 1989;Fowler et al, 1999).…”
Section: Using the Maab Pipeline To Identify And Classify Hrgps In Trsupporting
confidence: 86%
See 1 more Smart Citation
“…The majority of CL-EXTs identified in Arabidopsis are not predicted to be GPI-anchored (see Table I and Supplemental Table S2 in Johnson et al, 2017), and consistent with this, only a few GPI-anchored EXTs (class 9) were observed in Phytozome and 1KP data. Only one class, GPI-anchored PRPs (class 14), had no representatives from any 1KP group, which is consistent with our current, albeit limited, knowledge of PRPs (Averyhart-Fullard et al, 1988;Datta et al, 1989;Fowler et al, 1999).…”
Section: Using the Maab Pipeline To Identify And Classify Hrgps In Trsupporting
confidence: 86%
“…Investigation of PRPs has largely been restricted to legumes and Arabidopsis, where they have been shown to be minimally glycosylated, if at all (Averyhart-Fullard et al, 1988;Datta et al, 1989;Kleis-San Francisco and Tierney, 1990;Lindstrom and Vodkin, 1991;Fowler et al, 1999). The majority of PRPs are chimeric, as they contain an Ole PFAM domain, and they have been implicated in roles in root development (Bernhardt and Tierney, 2000), stress responses (Li et al, 2016), fiber development (Xu et al, 2013), and nodule formation .…”
mentioning
confidence: 99%
“…the Gly-rich proteins and the PRPs (Johnson et al, 2002). The 50% PAST threshold for identifying AGPs did not pick up many of the PRPs previously identified in Arabidopsis (Fowler et al, 1999). The reason for this is that the PAST percentage of PRP1 through PRP4 ranges from 32% to 45%.…”
Section: Other P/hrgps In Arabidopsismentioning
confidence: 94%
“…Judging from their tissue-specific expression, it is argued that extensins and Pro-rich proteins are "tailored to the tissue" during embryogenesis (Zhang et al, 2008) and throughout development (Fowler et al, 1999); this includes root hair formation (Bucher et al, 2002), which also involves a LRX1, a chimera of extensin and Leu-rich repeat protein (Baumberger et al, 2001).…”
Section: What Is the Role Of P3-type Extensin?mentioning
confidence: 99%